Pengaruh Ukuran Perusahaan, Profitabilitas, Laverage, Dan Ukuran Dewan Komisaris Terhadap Pengungkapan Corporate Social Responsibility - Ana Bariroh; Faizal Satria Desitama (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research is motivated by the existence of problems regarding negligence in implementing CSR and the concept of the need for companies to build harmonious relationships with the community and their stakeholders. This study aims to show how the influence of company size, profitability, leverage, and the size of the board of commissioners affects the disclosure of corporate social responsibility. In this study, the number of samples was 13 companies in the various industrial sectors listed on the IDX for 2019-2021. The method of determining the sample in this study used a purposive sampling method. The data used is secondary data, including annual report data on the company. The data analysis method uses panel data regression using the E-views 9 application. The results of this study indicate that partially company size, profitability and leverage do not have a significant effect on CSR disclosure. The size of the board of commissioners partially has a significant positive effect on CSR disclosure. Simultaneously, company size, profitability, leverage, and board size affect CSR disclosure by 25.7% and the remaining 74.3% is explained by other variables that are not included in the estimation of this study (error term). Keywords: Company Size, Profitability, Leverage, Size of the Board of Commissioners, Disclosure of Corporate Social Responsibility